HIGHLY SECURE AND RELIABLE USER IDENTIFICATION BASED ON FINGER VEIN PATTERNS (Global Journals of Research in Engineering, 2011)
With the evolution of consumer electronics technologies, personal information in consumer devices is becoming increasingly valuable. To protect private information from misuses due to the loss or theft, secure user identification mechanisms should be equipped into the consumer devices. Biometrics based personal identification is regarded as an effective method for automatically recognizing, with a high confidence, a person#x2019;s identity. A new biometric approach to the personal identification using finger-vein technology. The aim of this paper presents a user identification system framework using finger-vein technology for consumer electronics devices. The finger-vein identification is one of the biometrics sensor technologies, which provides high security and reliability than other identification technology. This paper proposes the Radon transform and Principal component analysis algorithms for the feature extraction and normalized distance measure for classification. The results show that the proposed system achieves good performance in terms of the false rejection rate and the false acceptance rate.